PCs for AP and other EM reflections. - Miller, Edmund K. (IEEE Antennas & propagation magazine.)
After a brief introduction to far field analysis of radiation sources (FARS), the author discusses its extension to the time domain (TDFARS) and the validation of CEM results. Other topics discussed include: EM transient analysis, software verification and validation, and error analysis.